2022
DOI: 10.3390/jcm11030666
|View full text |Cite
|
Sign up to set email alerts
|

Taurine and Its Derivatives: Analysis of the Inhibitory Effect on Platelet Function and Their Antithrombotic Potential

Abstract: Taurine is a semi-essential, the most abundant free amino acid in the human body, with a six times higher concentration in platelets than any other amino acid. It is highly beneficial for the organism, has many therapeutic actions, and is currently approved for heart failure treatment in Japan. Taurine has been repeatedly reported to elicit an inhibitory action on platelet activation and aggregation, sustained by in vivo, ex vivo, and in vitro animal and human studies. Taurine showed effectiveness in several p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 164 publications
(214 reference statements)
0
6
0
Order By: Relevance
“…Taurine has been repeatedly reported to cause inhibitory effects on platelets’ activation and aggregation in vitro and in vivo animal and human studies. [ 44 ] In this study, we found that the level of taurine in CBH group was significantly downregulated compared with Model group, suggesting the platelets activation promoted by CPO‐CDs. Taken together, from the perspective of metabolomics, plasma metabolic profiles of mice in NC, Model, and CBH groups were compared, and potential biomarkers such as phenylalanine, histamine, and taurine related to coagulation process were identified in rat plasma.…”
Section: Resultsmentioning
confidence: 66%
“…Taurine has been repeatedly reported to cause inhibitory effects on platelets’ activation and aggregation in vitro and in vivo animal and human studies. [ 44 ] In this study, we found that the level of taurine in CBH group was significantly downregulated compared with Model group, suggesting the platelets activation promoted by CPO‐CDs. Taken together, from the perspective of metabolomics, plasma metabolic profiles of mice in NC, Model, and CBH groups were compared, and potential biomarkers such as phenylalanine, histamine, and taurine related to coagulation process were identified in rat plasma.…”
Section: Resultsmentioning
confidence: 66%
“…Taurine inhibits the aggregation induced by adenosine diphosphate [232]. Hence, coadministration of ASA and taurine might have some benefits in antithrombotic therapy [233], with a possible effect on ASA resistance [231].…”
Section: Associated Dietary Compounds Taurinementioning
confidence: 99%
“…Intriguingly, this amino acid exhibits important antioxidant properties, Taurine has been extensively studied to determine its effects on human health. In terms of cellular function, taurine is primarily found in the intracellular fluid of many tissues, where it plays a vital role in a number of physiological processes [22][23][24][25][26][27][28]. It acts as an osmolyte, regulating cell volume and maintaining cell integrity [29,30].…”
Section: Tissuementioning
confidence: 99%